Secure and Efficient Control Transfer for IoT Devices - Zhi Wang; Han Ding; Jinsong Han; Jizhong Zhao (International Journal of Distributed Sensor Networks)
The prevalence of Internet of Things (IoT) requires flexible and fine-grained controls over the IoT devices. Existing works rely on specific controllers or programs to remotely control IoT devices, which is inefficient to support intelligent control in IoT environments. In contrast, utilizing a common portal device, for example, smart phone, to control variant IoT devices is a promising solution. However, it is challenging to guarantee the security when transferring the control of IoT devices. In this paper, we design a lightweight protocol to enable secure control transfer among the IoT devices, portal devices, and backend server. We demonstrate the effectiveness of our protocol in defending against mainstream attacks. Experimental results show the efficiency of our protocol in the authentication and key-updating during the control transfer.